13C- and 1H-NMR studies of oxyanion and tetrahedral intermediate stabilization by the serine proteinases: optimizing inhibitor warhead specificity and potency by studying the inhibition of the serine proteinases by peptide-derived chloromethane and glyoxal inhibitors. (22nd May 2007) - Malthouse, J.P.G.
Abstract : Catalysis by the serine proteinases proceeds via a tetrahedral intermediate whose oxyanion is stabilized by hydrogen-bonding in the oxyanion hole. There have been extensive 13 C-NMR studies of oxyanion and tetrahedral intermediate stabilization in trypsin, subtilisin and chymotrypsin using substrate-derived chloromethane inhibitors. One of the limitations of these inhibitors is that they irreversibly alkylate the active-site histidine residue which results in the oxyanion not being in the optimal position in the oxyanion hole. Substrate-derived glyoxal inhibitors are reversible inhibitors which, if they form tetrahedral adducts in the same way as substrates form tetrahedral intermediates, will overcome this limitation. Therefore we have synthesized 13 C-enriched substrate-derived glyoxal inhibitors which have allowed us to use 13 C-NMR and 1 H-NMR to determine how they interact with proteinases. It is hoped that these studies will help in the design of specific and highly potent warheads for serine proteinase inhibitors.